1979
DOI: 10.1021/bi00583a016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a precursor form of stratum corneum basic protein in rat epidermis

Abstract: The fully differentiated anucleate cells of the stratum corneum of newborn rat epidermis contain a cationic protein called stratum corneum basic protein (SCBP). This protein has a molecular weight (49 000) and an amino acid composition similar to a protein extracted from the less differentiated cell layers of the epidermis. Pulse--chase experiments with radiolabeled histidine were undertaken to test the possiblity that SCBP is derived from a preexisting protein. A protein of 52 000 daltons is rapidly but trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…In concert with these observations were the biochemical data which revealed that histidine-rich, basic protein in the keratohyalin granule was a high molecule weight, phosphorylated, polymeric precursor (now called profilaggin [45]) of the immunologically cross-reactive protein in the stratum corneum cell [46][47],…”
Section: -D Reconstructionmentioning
confidence: 99%
“…In concert with these observations were the biochemical data which revealed that histidine-rich, basic protein in the keratohyalin granule was a high molecule weight, phosphorylated, polymeric precursor (now called profilaggin [45]) of the immunologically cross-reactive protein in the stratum corneum cell [46][47],…”
Section: -D Reconstructionmentioning
confidence: 99%
“…Ball et al [l] found that the granular cell HRP (HRPJ extracted in a heterogeneous molecular weight form (between 60-1,OOO K) and suggested that it was a polymer of various numbers of subunits of an earlier precursor (HRP,). Dale and Ling [9] and Lonsdale-Eccles et al [15], on the other hand, isolated granular cell HRP in the form of a stable 53 K phosphoprotein, although this had a strong tendency to polymerise. In contrast, it has been shown [21] that a single phosphorylated polypeptide of very high molecular weight accounts for the majority of the granular cell HRP in neonatal rat and adult guinea pig epidermis, under extraction conditions which minimise protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylamide gels (7.5%) were prepared before use as described by Fairbanks et al (18) with slight modification (concentration of 50S, 0.1 %). The four major bands in epidermal homogenates were identical to those of fibrous keratin proteins extracted by the method of Dale et al (19) as described previously (20,21). The gels were dried on Whatman No.…”
Section: Methodsmentioning
confidence: 98%